Análise da prática de esterilização de materiais em um hospital de grande porte: subsídios para uma gestão da prática organizacional - Panazzolo, Giovanni Augusto Kalempa (2019)
With the proximity between health care and management areas, new debates, inquiries and results can be obtained, benefiting both. However, this approach should be careful and needs effective methodologies to make changes in these areas. From this need, this research aimed to gather health care and management areas through theory of practices. In this sense, the aim was to characterize how sterilization practices were developed at a material sterilization center in a large philanthropic hospital. Literature review showed a gap in the use of practical approach in the understanding of changes in hospitals organization. Qualitative method based on the empirical approach through interviews with the actors involved in hospital materials sterilization practice were used. Data analysis was oriented by sensitizing concepts proposed by Nicolini (2012). Since insertion of ANVISA resolution, it was observed that the norms implemented for material sterilization triggered behavioral changes over time, with a slow and gradual process of developing new performances, but not without their own ruptures and contradictions of the networks of social relations of the organizational everyday The approach of theories of practice was sensitive to the apprehension of cultural change processes. The reflection obtained from this result is that training, physical structure, teamwork and change in practices were fundamental for transforming effectively this scenario.